2012
DOI: 10.1002/aic.13886
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of surface oxygen‐containing functional groups and their effect on adsorptive denitrogenation of liquid hydrocarbons over activated carbon

Abstract: The objective of this study is to get a fundamental understanding of role of surface oxygen-contained functional groups (OCFG) in adsorptive denitrogenation (ADN) of liquid hydrocarbons over activated carbon, and thus to improve the ADN performance of activated carbon through modification of surface chemistry of activated carbon. A set of activated carbon samples with different amount and distribution of OCFG was prepared by oxidative modification and thermal treatment of a commercial activated carbon. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…24 The modified sample was collected by filtration and washed with abundant deionized water till reaching neutral. 24 The modified sample was collected by filtration and washed with abundant deionized water till reaching neutral.…”
Section: Carbon Adsorbents and Oxidation Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…24 The modified sample was collected by filtration and washed with abundant deionized water till reaching neutral. 24 The modified sample was collected by filtration and washed with abundant deionized water till reaching neutral.…”
Section: Carbon Adsorbents and Oxidation Treatmentmentioning
confidence: 99%
“…This deconvolution method has been widely used for different carbon materials, such as the activated carbon, 44 carbon nanofibers, 47 carbon nanotubes, and carbon xerogels. 24 The deconvolution results of CO 2 and CO for OAC are shown in Figures 3c and 3d. 24 The deconvolution results of CO 2 and CO for OAC are shown in Figures 3c and 3d.…”
Section: Characterization Of the Ocfgs On Adsorbent Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The dibenzothiophene (DBT) capacity of a (NH 4 ) 2 S 2 O 8 oxidized AC was found to increase by 74 %, compared to that of the original AC . Li et al also reported that the adsorption capacities of a carbon sorbent for N compounds, especially the basic N compounds, were effectively enhanced after (NH 4 ) 2 S 2 O 8 oxidation . However, in these studies, the model diesels only contained singular type of species, i.e., either N or S compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed (NH 4 ) 2 S 2 O 8 performed better than HNO 3 and H 2 SO 4 in the denitrogenation of light cycled oil (LCO) for the studied carbon . The performance of (NH 4 ) 2 S 2 O 8 oxidized AC in the adsorptive removal of N or S compounds from model diesel fuels has been tested . The dibenzothiophene (DBT) capacity of a (NH 4 ) 2 S 2 O 8 oxidized AC was found to increase by 74 %, compared to that of the original AC .…”
Section: Introductionmentioning
confidence: 99%